2017
DOI: 10.1186/s12955-017-0736-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding polycystic ovary syndrome from the patient perspective: a concept elicitation patient interview study

Abstract: BackgroundThe aim of this study was to explore the need for a new disease-specific patient reported outcome (PRO) measure for use in clinical trials of drugs designed to target the underlying causes of polycystic ovary syndrome (PCOS), and in the process contribute to our understanding of the symptoms and impacts that define the patient experience with PCOS.MethodsSemi-structured interviews were conducted in 20 women diagnosed with PCOS according to the Rotterdam criteria who had not menstruated in the previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
(39 reference statements)
0
22
0
2
Order By: Relevance
“…28 Whether the cognitive issues reported by the participants in this study are attributable to age, anemia, 29 The sample size used for this study is typical of concept elicitation interview studies. 22,30,31 Achievement of conceptual saturation in this study indicates that the sample size was sufficient to characterize the burden of PK deficiency from the perspective of patients. It also indicates that it is unlikely any comorbidities or misdiagnoses were the cause of concepts such as jaundice that were reported and also appear in other conditions.…”
Section: Discussionmentioning
confidence: 87%
“…28 Whether the cognitive issues reported by the participants in this study are attributable to age, anemia, 29 The sample size used for this study is typical of concept elicitation interview studies. 22,30,31 Achievement of conceptual saturation in this study indicates that the sample size was sufficient to characterize the burden of PK deficiency from the perspective of patients. It also indicates that it is unlikely any comorbidities or misdiagnoses were the cause of concepts such as jaundice that were reported and also appear in other conditions.…”
Section: Discussionmentioning
confidence: 87%
“…Women’s health and its determinants are the subject of numerous studies worldwide [ 2 , 5 , 8 , 10 , 11 , 13 , 14 ]. PCOS is a disease with a complex symptomatology and diverse clinical presentations, which significantly affects the patients’ life and functioning [ 2 , 3 , 8 ]. Research shows that PCOS adversely affects women’s quality of life, wellbeing, self-esteem, psychological status, and body image [ 3 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is one of the most common endocrinopathies in women of reproductive age. Its etiology is not yet fully understood [ 1 , 2 , 3 ]. In accordance with the Rotterdam criteria, PCOS is diagnosed if two out of the following three findings are present: oligomenorrhea or oligo-ovulation, clinical or biochemical hyperandrogenism, and polycystic ovaries on ultrasound [ 1 , 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amiri, Tehrani, Esmailzadeh, Tohidi, Azizi and Basirat in 2018 [9] calculated the relationship between PCOS and Sexual function and found that 45.75% of the PCOS women met the criteria for sexual dysfunction. The literature suggests that the physical, medical and psychological symptoms of PCOS significantly affect the quality of life and satisfaction with life of such women [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%